Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Karyawan Honorer di Puskesmas Kota Banjarmasin - Ahmad Zaky Ihnadi; Azura Arisa; Muhammad Noor Aditya Pratama; Tut Barkinah (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2026)
This study aims to examine and analyze the effect of work motivation and work discipline on the performance of honorary employees. The population in this research consists of all honorary employees at Pekauman Health Center, Teluk Tiram Health Center, Cempaka Health Center, Alalak Selatan Health Center, and Terminal Health Center in Banjarmasin City. The sample used in this study consisted of 59 respondents, selected using a total sampling technique. The data were analyzed using multiple linear regression and the coefficient of determination with SPSS 26. The results showed that partially, work motivation had a positive and significant effect on performance (regression coefficient = 0.408; p = 0.001), while work discipline also had a positive and significant effect on performance (regression coefficient = 0.275; p = 0.013). The adjusted R-square value is 0.323, meaning that work motivation and work discipline contribute 32.3% to performance, while the remaining 63.7% is explained by other variables not examined in this research.